Study of the Influence of Work Ability, Work Motivation and Work Procedure Principles on Employee Performance - Samrika, Samrika; Idrus, Muhammad Ikram; Rizal, Samsul (Borong Newinera Publisher, 2025)
This study aims to examine and explain the influence of each variable of work ability, work motivation, and principles of work procedures on employee performance in the Regional Secretariat of Sinjai Regency. The type of research used is quantitative with data collection through questionnaires distributed to 97 employees. Data analysis was carried out using multiple linear regression to test the proposed hypothesis. The results of the study indicate that 1) Work ability has a positive and significant effect on employee performance. 2) Work motivation has a positive but not significant effect on employee performance, and 3) Work procedures have a positive and significant effect on employee performance.